2021
DOI: 10.1039/d1qo00643f
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous assembly of a (pseudo)rotaxane with a donor–π–acceptor axis formed by a Knoevenagel condensation

Abstract: The incorporation of a linear D-π-A “push-pull” chromophore synthesized by a Knoevenagel condensation as axle of a rotaxane is reported. While the introduction of the mechanical stoppers by the reversible...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…Intriguingly, we had previously confirmed that the bulk of the triazol-propylsulfonate groups on the chromophore suffice to mechanically interlock a rotaxane. 26 We anticipated 6 to be of similar size but probably underestimated the role of the ionic subunits in the mechanical fixation in solution. However, it appears that the macrocycle can pass the stopper subunit of 6 already at room temperature.…”
Section: Resultsmentioning
confidence: 97%
See 4 more Smart Citations
“…Intriguingly, we had previously confirmed that the bulk of the triazol-propylsulfonate groups on the chromophore suffice to mechanically interlock a rotaxane. 26 We anticipated 6 to be of similar size but probably underestimated the role of the ionic subunits in the mechanical fixation in solution. However, it appears that the macrocycle can pass the stopper subunit of 6 already at room temperature.…”
Section: Resultsmentioning
confidence: 97%
“…22,23 Stoppers at the ends of the rod mechanically interlock the dicationic macrocycle M. We chose the Diederich-type cyclophane M 24,25 due to its permanently charged piperidinium groups, the high association constants it exhibits in water, its ability to change emission properties of guests, as well as the ease of analysis by NMR due to its high symmetry and significant changes in chemical shifts upon complexation. [26][27][28][29][30] As additional water solubilizing groups anionic sulfonates were considered, pulling the rod towards the cathode and thereby supporting an upright arrangement of the rotaxane immobilized on the anode.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations